DAKWAH DAN PENGEMBANGAN MASYARAKAT - Sya'roni Tohir (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2020)
Community development is an effort to improve the social strata of community life from education, economy and social culture. If we relate it to da'wah, then community development is part of da'wah's work. Why does the writer say part of preaching work? Because preaching work is broader than just community development. Da'wah is to invite people to the goodness (all goodness). What is good is improved to be better. The point of preaching is to make multi-dimensional improvements. The dimension of the relationship between the servant and his Lord and the dimension of the relationship between the servant and the servant. And the relationship between the servant and himself. Like the dimension of monotheism, knowledge, economy, health, law, human rights and culture. If we observe the things done by community development activists, then we can conclude that the concepts that are carried out in the efforts of community development are part of the concept of da'wah. If so, then the concept of community development is the concept of da'wah.